Real-Time IoT Temperature Monitoring Using Xiaomi Mijia BLE, ESP32, MQTT, and EMQX - Andicho Haryus Wirasapta; Tiara Deta Pamungkas (Journal of Applied Electrical Engineering, 2026)
This paper proposes a low-cost IoT-based real-time temperature and humidity monitoring system as a Bluetooth Low Energy (BLE) to MQTT bridge using an ESP32 microcontroller, Xiaomi Mijia LYWSD03MMC sensor, and EMQX broker. The key novelty of this work lies in the quantification of end-to-end communication performance of a BLE–Wi-Fi–MQTT bridge architecture using commercial off-the-shelf components. Five repeated measurement trials were conducted to evaluate system performance. Results show a mean end-to-end latency of 318 ms (standard deviation: 16,4 ms, max: 342 ms), a packet delivery ratio of 99,6%, and a sensor accuracy of RMSE=0,22°C against a calibrated digital reference thermometer. The system operated continuously for 48 hours with 99,6% uptime and a single automatic reset. Compared to HTTP-based counterparts, the proposed BLE–MQTT bridge achieves 36,6% lower latency. These results confirm the feasibility of integrating proprietary BLE sensors into mainstream MQTT-based IoT platforms using a lightweight and replicable architecture.